Геопсихічні реакції і вдача українця - Рибчин, Іван (Психологія і суспільство, 2024)
У змістовно ємному і структурно компактному дослідженні українського достойника-патріота, професора Івана Рибчина (1892-1970) висвітлюється одна із найфундаментальніших ознак українського характеру і водночас найяскравіших граней національного духу – первинний уплив геопсихічних чинників (рідної природи, землі, краєвиду) на формування різнобарвної, самобутньої і суперечливо згармонізованої вдачі-долі українця. Переконливо доведено, що саме геопсихічні реакції, будучи спричинені географічним середовищем-ландшафтом, зумовлюють той чи інший, у деталях та особливостях, перебіг психодуховних процесів, станів, властивостей, тенденцій людини, котрі у взаємодоповненні формують те, що називається характером, вдачею, душею. Автор уповні аргументовано виокремлює й схарактеризовує ч о т и р и форми узалежнення останніх од просторово-рельєфних інваріантів українських земель, умотивовано стверджуючи, що психічні п е р е ж и в а н н я українців: а) низової степової смуги є уявно збагаченими динамічним матеріалом у нескінченну далечінь, глибше розмаїтими на відчування маєстатичного й необмеженого, розгорнено інтенсивними емоційно та ефективно через переключення уваги на відсутність зовнішніх змислових спонук і посилювальними вольовий потенціал степовиків канали розвитку диспозицій до вибухових учинкових акцій, які вирізняються високою динамікою психічного напруження і короткочасним триванням; б) смуги лісостепових височин, завдяки м’якости і лагідности хвилястої лінії краєвиду, стимулюють й унапрямлюють розвиток в українського етносу диспозиції до настрою життєрадісности і взаємодоповнення раціональної та естетичної настанови в екзистенційному утвердженні повсякдення; в) смуги лісистих північних і північно-західних низовин, головно через темряву лісових гущавин, усталюють і закріплюють диспозиції до вчування у таємничість лісової природи та інтимно дружнього відношення до лісу як свого вірного захисника у боротьбі за виживання і процвітання народу; г) гірське довкілля Карпат та інших узгір’й сприяють поступливости, життєрадісности і готовности потурати неопанованій інтенсивності вибухів пристрастей і, крім того, гра світла і тіней та барвистість мінливих гірських краєвидів унаснажує до відповідних естетичних диспозицій. In a content-rich and structurally compact study of the worthy Ukrainian patriot, Professor Ivan Rybchyn (1892 – 1970) one of the most fundamental features of the Ukrainian character and at the same time the brightest aspects of the national spirit is highlighted – the primary influence of geopsychological factors (native nature, land, landscape) on the formation of a colorful, the original and contradictory harmonized character-destiny of a Ukrainian. It has been convincingly proven that precisely the geopsychic reactions, being caused by the geographical environment-landscape, determine one or another, in details and features, the course of psycho-spiritual processes, states, properties, tendencies of a person, which mutually form what is called character, disposition, soul. The author, in a fully reasoned way, singles out and characterizes the f o u r forms of dependence of the last odes of the Ukrainian lands’ spatial-relief invariants, motivatedly arguing that the mental e x p e r i e n c e s of Ukrainians: a) from the lower steppe strip are imaginatively enriched with dynamic material into an infinite distance, more deeply diversified to feel the majestic and unlimited, expanded by intense emotionally and effectively through a shift of attention to the absence of external thought motives and amplifying the volitional potential of the steppes channels for the development of dispositions to explosive deed actions, which are distinguished by high dynamics of mental stress and short-term prolongation; b) from the strips of forest-steppe highlands, thanks to the softness and gentleness of the wavy line of the landscape, stimulate and direct the development of the disposition in the Ukrainian ethnic group towards the mood of cheerfulness and the complementarity of rational and aesthetic guidance in the existential affirmation of everyday life; c) from the strips of forested northern and northwestern lowlands, mainly because of the darkness of the forest thickets, establish and consolidate dispositions for learning in the mystery of forest nature and intimately friendly attitude to the forest as their faithful defender in the struggle for the survival and prosperity of the people; d) from the mountain environment of the Carpathians and other hills contribute to the compliance, cheerfulness and willingness to indulge the uncontrolled intensity of the explosions of passions and, in addition, the play of light and shadows and the colorfulness of the changing mountain landscapes inherit the corresponding aesthetic dispositions.